Discovering non-random segregation of sister chromatids: the naïve treatment of a premature discovery - Lark, Karl G. (Frontiers in Oncology, 2013)
The discovery of non-random chromosome segregation is discussed from the perspective of what was known in1965 and1966. The distinction between daughter, parent or grandparent strands of DNA was developed in a bacterial system and led to the discovery that multiple copies of DNA elements of bacteria are not distributed randomly with respect to the age of the template strand. Experiments with higher eukaryotic cells demonstrated that during mitosis Mendel’s laws were violated; and the initial serendipitous choice of eukaryotic cell system led to the striking example of non-random segregation of parent and grand-parent DNA template strands in primary cultures of cells derived from mouse embryos. Attempts to extrapolate these findings to established TC lines demonstrated that the property could be lost. Experiments using plant root tips demonstrated that the phenomenon exists in plants and that it was, at some level, under genetic control. Despite publication in major journals and symposia (Lark et al. (1966a); Lark (1967a; 1967b; 1969, 1969a; 1969b)) the potential implications of these findings were ignored for several decades. Here we explore possible reasons for the pre-maturity (Stent, 1972) of this discovery.